Descrição da larva de Popanomyia femoralis Kertész, 1909 e do pupário de Engicerus major Lindner, 1964 (Diptera, Stratiomyidae) - Xerez, Roberto de (2003)
The larva of Popanomyia femoralis and puparium of Engicerus major are described. The larvae were collected under the bark of fallen trees in an area near the tropical rain forest at Ilha da Marambaia (23º 04'15''S-43º53'59''W-sea level) and Cabo Frio (22º52'46''S-42º01'07''W-4 m), State of Rio de Janeiro, Brazil. Biological notes are presented. The larva of Popanomyia femoralis and puparium of Engicerus major are compared with those of Chalcidomorphina aurata Enderlein, Cosmariomyia argyrosticta Kertész, Dactylodeictes lopesi Lindner and Vittiger schnusei Kertész, other species of the same subfamily.